Peradaban Islam di Afrika Utara (Kerajaan Murabitu dan Muhabittun) - Dais, Sudirman; R, Rani; Sulaiman, Umar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
North Africa is a region that is in the middle between the East and West parts of Africa, this geographical location was one of the reasons why during the time of Umar Bin Khattab he expanded into the region, because it was thought that it would be easy to strengthen political power because the region was a link between the continents of Asia and Europe, therefore Islamic civilization which began during the time of Umar Bin Khattab was very developed in the North African region until the Khalifa after that, then the Umayyad and Abbasid dynasties. One of the most famous civilizations is how Muslims were able to control one part of the European continent. namely Andalusia, which at that time was the North African region controlled by the Muwahiddun dynasty, which was a kingdom formed as a result of the weakening or decline of the Abbasid dynasty. During the reign of these two kingdoms, many civilizations gave birth, one of which was the use of the gold dinar for the first time and many more.